Role of Per Operative Use of Intravenous Magnesium in Reducing the Incidence of Per and Post Operative Arrhythmias in Conventional Coronary Artery Bypass Graft Surgery - Alam, MMU; Ahsan, MN; Rahman, MMM; Khan, M; Hossain, MM; Tauhid-Ul-Mulk, M; Sultana, MS (Journal of Armed Forces Medical College, Bangladesh, 2014)
Introduction: Arrhythmias are not uncommon after Coronary Artery Bypass Graft (CABG) surgery. There is increasing evidence that Magnesium, the important intracellular cation plays a crucial role in preventing and terminating cardiac arrhythmias. Objectives: The aim of this study was to establish the role of peroperative use of intravenous Magnesium in reducing the incidence of per and postoperative arrhythmias in CABG surgery. Materials and methods: A total sixty (Group-I 30 and Group-II 30) patients of both sexes and different ages undergoing conventional CABG surgery under general anesthesia in CMH Dhaka from January 2009 to December 2011 were selected randomly. After induction, Group-I received 2 gm of Magnesium in 100 ml normal saline intravenously over a period of 30 minutes and Group-II received no Magnesium. Parameters recorded per and postoperatively were- aortic cross clamp time, Cardio Pulmonary Bypass (CPB) time, total surgery time, Heart Rate (HR), Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP) and blood sample were collected on arrival to Cardiac Intensive Care Unit (CICU) and after 6, 12, and 24 hours. Results were expressed as mean ± SD (Standard Deviation) or in frequencies (percentage) as applicable. The results were analyzed by Students t test. Results: Magnesium levels were significantly (p<0.05) low in Group-II patients than that of Group-I. In Group-II patients, the fluctuations of HR, SBP and DBP were significantly (p<0.05) more than that of Group-I. In Group-I patients incidence of arrhythmias were significantly (p<0.05) less than that of Group-II. Conclusion: Low serum Magnesium levels are a frequent finding after conventional CABG surgery. This acute loss of Magnesium has been suggested as an etiology of many per and postoperative arrhythmias. This study revealed that peroperative administration of Magnesium provided a significant reduction in arrhythmias per and postoperatively. DOI: http://dx.doi.org/10.3329/jafmc.v9i1.18739 Journal of Armed Forces Medical College Bangladesh Vol.9(1) 2013: 105-114